Retraction: Promoting the Safe and Strategic Use of Technology for Victims of Intimate Partner Violence: Evaluation of the Technology Safety Project (Violence Against Women, 2009)
This article has been withdrawn because it is a redundant publication of an article that was published in the Journal of Family Violence, Issue 1, Volume 24. January 2009, DOI: 10.1007/s10896-008-9207-2. The article went through peer review for publication in Violence Against Women without the journal_s knowledge that a similar article was submitted to the Journal of Family Violence.